Analisis Tingkat Kenyamanan Ruang Kuliah (Studi Kasus Pada Gedung D Universitas Tribhuwana Tunggadewi Malang) - Kaleka, Sarita Inya ; wijaya, Handika Setya ; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Tribhuwana Tunggadewi University is one of the campuses in Malang City which is located on Jl. Telaga Warna, Tlogomas. The Unitri campus has several lecture buildings, namely building A (Rectorate), building B (lecture hall), building C (lecture hall) and building D (lecture hall). Building D is divided into several lecture halls, including D3 and D4 rooms. This research was conducted in the D33 lecture hall and D41 lecture hall in the D building. In this D building still uses a lot of windows that serve to facilitate light illumination and natural air entering. The purpose of his research was to find out the air conditioning system in the lecture hall in Building D, Analyze the air conditioning system according to SNI 03-6572-2001 in the lecture hall in Building D and provide a solution for the air conditioning system in the lecture hall in Building D. Data collection methods used with how to conduct observations and direct surveys at locations in the form of primary data and secondary data. From the results of the analysis above, it is obtained the comfort level of the lecture room based on the results of temperature measurements which prove that the temperature in the room does not meet SNI 03-6572-2001 and the results of respondent responses also show that many feel uncomfortable with the conditions of the lecture room D33 and D41.